Investing the use of portfolio as a tool to enhance students writing skill a case study in S.M. Sains, Kuching - Madihi, Hazali (University Malaysia Sarawak, UNIMAS., 2003)
The purpose of this study is to find out the potential of using portfolio as a tool to enhance students' writing skill and to identify the strength and constrains of using portfolio in their lesson. The sample used in this study area are ten English language teachers and five Form 2 students, in S.M. Sains, Kuching.